Learners’ Discussion Patterns, Perceptions, and Preferences in a Chinese Massive Open Online Course (MOOC) - Ouyang, Fan; Li, Xu; Sun, Dan; Jiao, Pengcheng; Yao, Jiajia (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
The development of massive open online courses (MOOCs) has proceeded through three generations, and in all three, online discussions have been considered a critical component. Although discussions in MOOCs have the potential to promote learning, instructors have faced challenges facilitating learners’ knowledge inquiry, construction, and management through social interaction. In addition, understanding various aspects of learning calls for more mixed-method studies to provide both quantitative, generalized analysis and qualitative, detailed descriptions of learning. This study fills these practice and research gaps. We designed a Chinese MOOC with the support of a pedagogical strategy, a learning analytic tool, and a social learning environment in order to foster learner engagement in discussions. Mixed methods were used to explore learners’ discussion patterns, perceptions, and preferences. Results indicated that learners demonstrated varied patterns, perceptions, and preferences, which implies a complex learning process due to the interplay of multiple factors. Based on the results, this research provided theoretical, pedagogical, and analytical implications for MOOC design, practice, and research.